Ideological and Political Education in Colleges and Universities Reshapes Marxist Belief - Zhang, Xiaoxiao (Journal of Theory and Practice of Social Science, 2024)
Strengthening the function of belief education in ideological and political theory courses in colleges and universities has important theoretical and practical significance. This paper investigates the status quo of college students' belief in the form of questionnaire, emphasizes the importance and urgency of strengthening college students' belief education, analyzes the lack of college students' belief education in ideological and political theory course, and probes into the ways of strengthening college students' belief education in ideological and political theory course. Marxist belief, the source of all revolutionary spirits in China, has played an important role in the process of revolution, construction, reform and development. However, since the reform and opening up, the changes in the international and domestic situation have made people have a strong ideological contrast, coupled with the impact of multiple beliefs, although Marxism as the dominant position in China's ideological field has not changed, but the phenomenon of social anxiety and anger caused by the crisis of faith has to cause deep thought.